(3UOM GdYfOdjH aj GdThb Edi GdMHjHs
(3ChdgG (B:s
(3MeOkG def CLdS YQGFS GdEaJcGQ Ydi efUGJ GdEHJcGQ CeG HYO agPg ChQGb LeYJgG MGdI GdEWdGb Yf YhGFb GdhKGb aJPcQJ eG cJHJg ef GdCTYGQ hCfTCJg ai eOGFM GdCNjGQ s
(3BNQgG (B:s
(3HTbjge hHCMeO PGc GdPi jOYi CHG WQWhQ ef MGei dRjeg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
Keywords: (3GdCOHs